A pegada hídrica das exportações agrícolas de Pernambuco - Rocha, Sérgio Rodrigues (2019)
Many countries with water shortages import increasing quantities of food. This acquisition product is virtually equivalent to import water, which otherwise, would be sued for the production of foods in countries buyers. The world food trade can save water resources, through virtual water transfers from countries very productive, in terms of water use, to other less productive. The water footprint methodology quantifies the total volume of fresh water needed for the production chain, in various locations around the world, of the goods and services consumed by a person, a region or a country, being an indicator of ownership of this uses direct and indirect of this natural resource. This study calculates the water footprint of products selected from the list of exports, from 1997 to 2010, of the agricultural sector of the state of Pernambuco. The result is very significant (13.5 billion cubic meters) to Pernambuco, located in the Brazilian semiarid. From the point of view of water management, reducing the water footprint of the Brazilian state, which presents serious problems of water scarcity, can be achieved through the use of new agricultural techniques that require less water resource per kilogram produced; as well as cause less environmental pollution.